Developing Intelligent GeoDashboard Platform for the Downstream of Nickel, Bauxite, Cobalt, and Silica: Systematic Literature Review - Andrea Sutanto; Raditya Tamam; Alexander Agung Santoso Gunawan (Bina Nusantara University, 2025)
Indonesia possesses abundant natural resources, including nickel, bauxite, cobalt, and silica, which are essential for industries such as battery production, construction, and green technology. To maximize their economic value, the Indonesian government has implemented downstream policies that require domestic processing before export. Effective resource management is crucial for the success of these policies and the national economy. This study conducts a systematic literature review to examine how downstream policies are implemented in different countries (RQ1), analyze cases of downstream disputes and their solutions (RQ2), and explore the impact of technology and Global Value Chains (GVCs) on these policies (RQ3). A structured methodology is used to collect and analyze relevant literature, highlighting best practices and key challenges. Findings show that countries with strong regulations and technological innovation achieve better downstream outcomes. Past disputes reveal the need for strategic policymaking and technological adaptation to avoid risks. In this context, the PetaHilirisasi platform offers a smart solution by integrating geospatial technology and artificial intelligence to monitor and manage mineral resources efficiently. This platform helps optimize downstream processes, improve operational efficiency, and reduce environmental impact. PetaHilirisasi demonstrates the potential of digital solutions in strengthening Indonesia’s downstream sector. By leveraging technology, Indonesia can enhance the value of its natural resources while promoting sustainable development in the mineral industry,